Strength of Reference Groups to Moderate Online Repurchase Intention on Generation X - Atmaja, Ni Putu Cempaka Dharmadewi; Puspitawati, Ni Made Dwi (International Journal of Applied Business and International Management, 2019)
The purpose of this study was to determine the role of the strength of the reference group in moderating the effect of e-commerce service quality and customer satisfaction on online repurchase intentions. The selected respondents were adolescents aged 17-24 years who were generation X. The study used primary data obtained from the results of questionnaires to 100 students who were educated in public universities in the city of Denpasar, Bali, Indonesia. Determination of the sample using purposive sampling. The data analysis technique used is by using this method of primary data collection using a questionnaire. Simple linear regression analysis and moderated regression analysis using the Statistical Product and Service Solution (SPSS) program. The results show that the quality of e-commerce services and customer satisfaction has a positive and significant effect on online repurchase intention. the strength of the reference group can strengthen the relationship between the quality of e-commerce services and the intention to repurchase. But the reference group cannot strengthen the relationship between customer satisfaction and the intention to repurchase. The implication in this study is that retailers must pay attention to the quality of e-commerce services so that they can provide convenience, comfort and security in shopping, giving rise to a strong intention to repurchase customers.